2003
DOI: 10.1088/0951-7715/17/1/003
|View full text |Cite
|
Sign up to set email alerts
|

Topological sequence entropy of interval maps

Abstract: We establish a full classification of chaotic and non-chaotic interval maps from the point of view of topological sequence entropy. This completes the papers of Franzová and Smítal (1991 Positive sequence topological entropy characterizes chaotic maps

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
17
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 15 publications
1
17
0
Order By: Relevance
“…We end this section with the following observation (we thank W. Huang for suggesting this question). In [28] the authors have shown that if T : [0, 1] −→ [0, 1] is a continuous map then T is null if and only if T is not chaotic in the sense of Li and Yorke; and in [18] the author has shown that h * top (T ) ∈ {0, log 2, ∞}. In fact we can prove the following:…”
Section: An Application To Interval Mapsmentioning
confidence: 93%
“…We end this section with the following observation (we thank W. Huang for suggesting this question). In [28] the authors have shown that if T : [0, 1] −→ [0, 1] is a continuous map then T is null if and only if T is not chaotic in the sense of Li and Yorke; and in [18] the author has shown that h * top (T ) ∈ {0, log 2, ∞}. In fact we can prove the following:…”
Section: An Application To Interval Mapsmentioning
confidence: 93%
“…A similar topological concept, called topological sequence entropy, was introduced and studied several years later by Goodman [25], who also investigated the relationship between his concept and the measure-theoretic analogue defined by Kushnirenko. After that there has been a significant activity in studying both kinds of sequence entropies -see for example [9,11,22,33].…”
Section: Introductionmentioning
confidence: 99%
“…By [14], T ∈ C(I) is Li-Yorke chaotic if and only if h * (T ) > 0. Due to [9], there are only three possibilities for T ∈ C(I), namely, h * (T ) is either 0 or log 2 or ∞. These facts are shown in Table 1.…”
mentioning
confidence: 99%
“…. } ∪ {∞} X finite sets, zero-dimensional spaces with finite derived sets [48] interval [9], circle [8], finite trees [42], finite graphs [43] zero-dimensional spaces with infinite derived sets [42], some dendrites [42], manifolds of dimension ≥ 2 [42] Table 2. Known values of S(X) Since every dendrite is an absolute retract for the class of all compact metric spaces [7], we in fact have S(X) = log N * not only for the manifolds with dimension ≥ 2, but for any compact metric space X containing the dendrite from [42].…”
mentioning
confidence: 99%